The Gambia : Requests for Disbursement Under the Rapid Credit Facility and Modification of Performance Criteria Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for The Gambia. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents The Gambia's Requests for Disbursement Under the Rapid Credit Facility and Modification of Performance Criteria Under the Extended Credit Facility Arrangement. The immediate challenge is to contain the spread of coronavirus disease 2019 (COVID-19), strengthen medical care, implement the social distancing and other containment measures, and mitigate the economic impact of the pandemic, especially on the most vulnerable. It is important to establish appropriate criteria and reporting requirements for the use of emergency spending and ensure that COVID-related operations and outlays undergo a full independent audit to enhance transparency. In order to safeguard debt sustainability, the authorities are encouraged to seek additional grant financing for emergency spending. The Central Bank of The Gambia should continue to monitor developments in the financial sector, to ensure adequate liquidity and oversight, while avoiding a blanket weakening of supervisory standards. A strengthening of market surveillance under the existing regulations will help detect and address appropriately any weakening of banks' foreign exchange positions. Maintaining a flexible exchange rate will help absorb balance-of-payments shocks.